To study the profile of patients with acute respiratory distress syndrome presenting in emergency of a sub-Himalayan region hospital - Krishna Bharath Reddy; Tarun Sharma; Aradhna Sharma; Kailash Sharma (Journal of Family Medicine and Primary Care)
Introduction: Acute respiratory distress syndrome (ARDS) is a life-threatening condition. ARDS carries a high mortality, and few effective therapeutic modalities exist to combat this condition. The etiology of ARDS can be expected to be different in India due to the higher incidence of tropical infectious diseases. However, not many studies have been done in India on ARDS. This study was planned to evaluate the epidemiological profile of patients with ARDS in a tertiary care hospital in the sub-Himalayan region of Himachal Pradesh, India. Methodology: It was a hospital based prospective study which was conducted in the department of medicine of Dr. Rajendra Prasad Government Medical College and Hospital, Kangra (at Tanda), a tertiary care referral hospital. Duration of study was 1 year, viz, January 2020 to January 2021. All patients above the age >18 who presented with ARDS satisfying the given definition presenting in Emergency of DRPGMCH Kangra were included in the study. Results: A total of 75 patients with ARDS admitted from emergency in various wards of the hospital after triaging. Our study observed that the cause of ARDS did not have a significant association with severity of ARDS (P = .209). We observed that among 30 patients with severe ARDS, 24 patients had involvement of all four quadrants and six patients had involvement of three quadrants. Involvement of all quadrants was significantly associated with a severe ARDS (P < .001). Requirement of inotropes was not significantly associated with the severity of ARDS (P = .669). We observed that the patients with severe ARDS had significantly lower levels of albumin in comparison to moderate and mild ARDS (P = .021). We observed that the patients with severe ARDS had significantly higher levels of PCT in comparison to moderate and mild ARDS (P < .0001). Conclusion: ARDS carries a very high mortality, irrespective of the cause and the risk factors that were associated with poor prognosis included older age, female sex, presentation during rainy seasons, high SOFA and APACHE II scores at the time of presentation, requirement of MV, requirement of early inotropes, high PCT levels, low albumin levels, and the severity of ARDS at presentation.